The Cory Aquino Leadership: Perspectives from the Social Sciences - Studies Center, Third World (Kasarinlan: Philippine Journal of Third World Studies, 2011)
Is there anything left for the social scientists to explain? What part of Corazon “Cory” Aquino have we not understood amidst the very public outpouring of grief and deep gratitude during her passing last August? The University of the Philippines (UP) Third World Studies Center (TWSC), together with the Office of the UP Diliman Chancellor, the UP Department of Political Science, and the Philippine Political Science Association organized this event to respond precisely to these concerns, which are borne out of cynicism and our haste to get over the former president’s death. The organizers believe that Cory Aquino’s life as a leader, her experiences, and the decisions she made that still strongly inform our society today were all drawn from a wide range and sometimes conflicting mix of personal convictions and political positions. Thus, to interpret her life in the same way we attempt to comprehend the nation’s sorrow over her death, there is a need for the different disciplines of the social sciences to come together and share their understanding of her life and legacy. Equally important is the opportunity that this forum provides to the current generation of students whose idea of her role in the nation’s history is only a faint approximation of what their elders have lived through. The forum challenges us to go beyond the narrow sentimentality of grief—that it be an occasion not only for old war stories but also for new inquiries about a past and a leader whom we have considered so deserving of our sacrifice, too worthy of our tears.